PERANAN PUBLIC RELATION DALAM MEMPERTAHANKAN CITRA BALI DYNASTY RESORT - Maya Kurniawati; Syofia Achnes (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
The purpose of this study was to describe the shape of the role played by the Public Relations of Bali Dynasty Resort in maintaining the image of Bali Dynasty Resort. Choosing Bali as a tourist destination worldwide daily visited by many tourists at home and abroad. In her choose Bali Dynasty Resort for a Resort that was established a long time and the only the concept "family resort" in the Kuta area, certainly a lot of competition and a heavy burden to maintain its image. This study used a qualitative approach with descriptive case study method. The subjects were Public Relation Bali Dynasty Resort and interested parties therein (Director of Sales and General Manager). While his research object is role in maintaining the image of Bali Dynasty Resort, informants were selected purposively. Data were collected through literature based on the theory, documentation, observation and in-depth interviews with open-ended type. The results showed that the Public Relation Bali Dynasty Resort running all four categories of roles based on the concept Dozier & Broom, namely as an expert adviser (Expert prescriber), facilitator of communication (communication facilitator), facilitator of the process of problem solving (problem solving process facilitator) and a communications technician (communication technician). According to General Manager and Director of Sales feedback received also a lot that is positive and produced many benefits to Bali Dynasty Resort. Keywords: Role of Public Relations, the image of Bali Dynasty Resort.